Rutin alleviated acrolein-induced cytotoxicity in Caco-2 and GES-1 cells by forming a cyclic hemiacetal product - Chen, Peifang; Liu, Shuang; Yin, Zhao; Liang, Pengjie; Wang, Chunhua; Zhu, Hanyue; Liu, Yang; Ou, Shiyi; Li, Guoqiang (Frontiers in Nutrition, 2022)
Acrolein (ACR), an α, β-unsaturated aldehyde, is a toxic compound formed during food processing, and the use of phenolics derived from dietary materials to scavenge ACR is a hot spot. In this study, rutin, a polyphenol widely present in various dietary materials, was used to investigate its capacity to scavenge ACR. It was shown that more than 98% of ACR was eliminated under the conditions of reaction time of 2 h, temperature of 80 ℃, and molar ratio of rutin/ACR of 2/1. Further structural characterization of the formed adduct revealed that the adduct of rutin to ACR to form a cyclic hemiacetal compound (RAC) was the main scavenging mechanism. Besides, the stability of RAC during simulated in vitro digestion was evaluated, which showed that more than 83.61% of RAC was remained. Furthermore, the cytotoxicity of RAC against Caco-2 and GES-1 cells was significantly reduced compared with ACR, where the IC50 values of ACR were both below 20 μM while that of RAC were both above 140 μM. And the improvement of the loss of mitochondrial membrane potential (MMP) by RAC might be one of the detoxification pathways. The present study indicated that rutin was one of the potential ACR scavengers among natural polyphenols.